Desenvolvimento e caracterização de nanofibras obtidas pela técnica de eletrofiação coaxial visando a liberação de bevacizumabe para o tratamento de degeneração macular relacionada a idade - Sarah Oliveira Lamas de Souza (2016)
The coaxial electrospinning is known as an efficient technique for manufacturing core-shell nanofibers. The coaxial electrospinning allows the encapsulation of fragile bioactive agents in water solutions and eliminates the harmful effects resulting from direct contact with solvents and adverse conditions during processing. The age-related macular degeneration (AMD) affects the central retina, the macula, and is the leading cause of blindness in people over 50 years old. Angiogenic factors have been associated with the neovascular process, which led to the use of antiangiogenic drugs, such as bevacizumab as the current treatment of this pathology. In this work, the technique of coaxial electrospinning was used to produce biodegradable core-shell nanofibers for incorporation and release of bevacizumab. Poly(caprolactone) and gelatin were used to form the shell of the nanofiber, while poly(vinyl alcohol) and bevacizumab were part of the core. Nanofibers were characterized by Scanning Electron Microscopy (SEM), thermogravimetry (TG) and Fourier transform infrared (FT-IR). The in vitro biocompatibilityantiangiogenic activity and the activity of bevacizumab were also evaluated. The obtained results proved the viability of the production of core-shell nanofibers having PCL/gelatin as the shell and PVA as the core material. The nanofibers showed no cytotoxicity to the cells, even in the presence of Bevacizumab. Bevacizumab maintained its antiangiogenic activity when incorporated into the system.